Brushless direct current (BLDC) motor driving experimental set - (:unkn) unknown (SILA SCIENCE, 2011)
The aim of the present study is to familiarize students with the parameters of a brushless direct current (BLDC) motor and its driving circuits, with particular emphasis on the dynamic motor behavior from stable working to the transient operating phase. A BLDC motor experimental set and MATLAB real time simulation program are designed and improved to control a BLDC motor's parameters in a laboratory environment. The characteristics of the operating parameters are mathematically and graphically presented in a trial. BLDC motor driving characteristics are given in detail to support students' theoretical understanding. This study is intended to provide to students with all the necessary theoretical knowledge including MATLAB real time simulation program, with the best practical observation on the subject. Furthermore, the driving circuit card is designed and constructed to provide to the students simple, clear and easily understood data for a general overview of BLDC motors.
Keywords: BLDC motor; Driving circuit design; Experiment set; MATLAB; SIMULATION; KNOWLEDGE; PHYSICS; DRIVES